Child Studies Multiple - Anna Sparrman; Yelyzaveta Hrechaniuk; Olga Anatoli Smith; Klara Andersson; Deniz Arzuk; Johanna Annerbäck; Linnea Bodén; Mindy Blaise; Claudia Castañeda; Rebecca Coleman; Florian Eßer; Matt Finn; et al. (Culture Unbound: Journal of Current Cultural Research, 2023)
This text is an exploration of collaborative thinking and writing through theories, methods, and experiences on the topic of the child, children, and childhood. It is a collaborative written text (with 32 authors) that sprang out of the experimental workshop Child Studies Multiple. The workshop and this text are about daring to stay with mess, “un-closure” , and uncertainty in order to investigate the (e)motions and complexities of being either a child or a researcher. The theoretical and methodological processes presented here offer an opportunity to shake the ground on which individual researchers stand by raising questions about scientific inspiration, theoretical and methodological productivity, and thinking through focusing on process, play, and collaboration. The effect of this is a questioning of the singular academic ‘I’ by exploring and showing what a plural ‘I’ can look like. It is about what the multiplicity of voice can offer research in a highly individualistic time. The article allows the reader to follow and watch the unconventional trial-and-error path of the ongoing-ness of exploring theories and methods together as a research community via methods of drama, palimpsest, and fictionary.